2020
DOI: 10.1080/10807039.2020.1768824
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazards, health conditions and personal protective equipment used among healthcare workers in hospitals, Thailand

Abstract: This cross-sectional study aimed to evaluate occupational hazards, health conditions and personal protective equipment used among healthcare workers. Information from the sample size of 1,128 healthcare workers were collected using questionnaires. The healthcare workers participated in this study were from five departments including inpatient, outpatient, surgery and anesthesia, nutrition service and hospital support services departments in five hospitals in Thailand. The results indicated that the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
18
0
2
Order By: Relevance
“…For data analysis, we grouped sometimes + regularly into an “ever” variable. This questionnaire has been previously used in other studies in Thailand [ 22 , 23 , 24 ], and it is available in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…For data analysis, we grouped sometimes + regularly into an “ever” variable. This questionnaire has been previously used in other studies in Thailand [ 22 , 23 , 24 ], and it is available in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…Musculoskeletal complications are common among the employees of dental hospitals ( 8 , 9 ). The effect of workplace hazards begins with the entry of a student into a dental college, with 79% of students complaining of back or neck pain at the undergraduate level in UK dental schools ( 8 , 10 ). However, the ( 11 ) reported that the effect of ergonomic involvement in managing musculoskeletal illnesses among dental professionals is insignificant ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational stress is psychosomatic stress related to one's job ( 16 ). Workplace stress usually comes from demands that don't match a person's abilities, knowledge, and skills ( 10 ). What one perceives as a threat or a danger can be perceived as a challenge or motivation by someone else ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The word "hazard" can be explained as an inherent property of an agent, or a situation having the potential to cause adverse effects when an organism, system or population is exposed to ergonomics and stress related conditions that can affect an individual 1 . Occupational hazards include all the risks which are faced as a consequence of the working environment of a certain job 2 .…”
Section: Introductionmentioning
confidence: 99%